The Application Of The Full Costing Method In Calculation Of The Corporate Price Of Production (Hpp) As The Basis For Determining The Selling Price In The Mini Three Putri Button Of Bengkulu City - Purnomo, Megi; Susanti , Neri; Melinda , Tri Febrina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of the study was to determine the calculation and determination of the full costing method through the calculation of the cost of production (HPP) as the basis for determining the selling price at the Mini Tiga Putri Peyek Business in Bengkulu City. The analytical method used in this study is a comparative descriptive method. Based on the calculation of the cost of production carried out by the Tiga Putri Mini Peyek Business, the city of Bengkulu, the cost of production of mini dents per pack is Rp. 8,547.-. and the determination of the selling price based on the market price of Rp. 20,000 so that the profit earned is Rp. 11,453 per pack. Based on the full costing method, the cost of production of mini dents per pack is Rp. 16,213,-. With the determination of the selling price of 25% of the cost of production, the total selling price of mini dents per pack is Rp. 20,000, - so that the profit earned is Rp. 3,787 per pack. There is a difference in the calculation of the cost of production between the company's calculation and the full costing method because the company's calculation does not include labor costs and factory overhead costs, even though the selling price is the same but the profits obtained by the company are much smaller when compared to the company's calculation.